Un indio camino a los altares: santidad e influencia inquisitorial en el caso del «siervo de Dios» Nicolás de Ayllón - Espinoza Rúa, Celes Alonso (2012)
This article sheds light on the indirect influence exercised by the Inquisition on the process of beatification of the «servant of God» Nicolas de Ayllon. Through the analysis of his hagiography, written by the Jesuit Bernardo Sartolo, this article will highlight the importance that this literary genre had in the process of establishing his reputation for sanctity. Furthermore, this article examines how the intervention of the Holy Office, which questioned the hagiography and the main witness of the process, Maria Jacinta de Montoya, cast many doubt son the image of the sanctity of Nicolas. The examination led to the discrediting of his reputation as a candidate for sainthood and the suspension of the process.